Hutang Piutang Dalam Islam: Kajian Kritik Hadis Tentang Penundaan Pembayaran - Hidayatulah; Tajul Arifin (Yayasan Cendekia Gagayunan Indonesia, 2025)
Debt is one form of muamalah permitted in Islam. It serves as an economic activity conducted by individuals to fulfill their needs. Islam provides clear guidelines and laws regarding debt, including the obligation to repay debts on time. This study aims to discuss hadiths on debt, focusing on the legal ruling concerning delaying debt repayment by those capable of paying, with reference to Hadith Bukhari No. 2400. The study employs a descriptive-analytical approach by collecting data from hadith compilations, commentaries (syarh), classical and contemporary fiqh books, as well as scholarly journals. The analysis involves stages of takhrij, sanad criticism, matan criticism, and commentary (syarh) discussion. The findings reveal that the hadith is authentic (sahih) in terms of both sanad and matan, emphasizing the legal implication that delaying debt repayment without a valid reason constitutes an act of injustice. This research highlights the importance of timely debt repayment as a trust in Islam, contributing to the development of fiqh muamalah literature and supporting a fair and responsible Islamic legal system.